Concordance between the indirect V.O2max value estimated through the distance in Yo-Yo intermittent recovery test level 1 and the direct measurement during a treadmill protocol test in elite youth soccer players - Cabrera Hernández, M. A.; Tafur Tascon, L. J.; Cohen, D. D.; García-Corzo, S. A.; Quiñonez Sánchez, A.; Povea Combariza, C.; Tejada Rojas, C. X. (Journal of Human Sport & Exercise, 2018)
The main aim of this study was to evaluate the concordance between the indirect V.O2max value estimated by the distance achieved in the Yo-Yo intermittent recovery test level 1 (YYIR1) and the direct measurement during a treadmill protocol test (TP) in elite youth soccer players. Methods: Fourteen elite under 20 year`s old soccer players from a first division soccer club were evaluated. Test were performed one week apart. In both tests V.O2, was measured with an ambulatory gas exchange measurement. YYIR1 estimated V?O2max was calculated using the equation described by Bangsbo et al. (2008) and in TP was calculated using American College of Sport Medicine equation. Results: Lin´s concordance correlation coefficient between direct V.O2max in TP and estimated V.O2max in YYIR1=0.271 (poor concordance). Conclusions: The poor concordance between direct and indirect V.O2max measurements in TP and YYIR1, indicated that in an elite population both test, are not good indirect predictors of V.O2max, reached in those tests using current predictive equations. The YYIR1 is well established as a performance-relevant test in elite players, but our data suggests that due to its poor concordance with imprecise estimation of V.O2max, which should be measured directly if this variable is of specific interest.